Welfare and care rights of the elderly in the light of evolving European system standards - Jimena Quesada, Luis (Política y Sociedad, 2023)
This essay tackles the protection of the elderly in the light of the evolving profiles of the European human rights system. Indeed, from a multilevel human rights protection perspective, the standards of both the Council of Europe and the European Union are analysed, with emphasis on the European Social Charter and the European Committee of Social Rights case law. Such analysis leads to the conclusion that a crucial European acquis of Ius Senectutis is being forged in the context of the health and humanitarian crisis caused by the covid-19 pandemic. European standards and their synergies with other international and national standards are ultimately called upon to optimise the rights of the elderly and their dignity in coherence with the pro personae principle.
Keywords: right to care; active ageing; non-discrimination on grounds of age; European Committee of Social Rights; most favourable European standard